The legal status of religious minorities in the countries of the European Union: proceedings of the meeting; Thessaloniki, November 19 - 20, 1993 (Pubblicazioni di diritto ecclesiastico, 1994)
Artikelverzeichnis: Barberini, Giovanni, La sitation juridique des minorités religieuses en Italie Basdevant-Gaudemet, Brigitte; Messner, Francis, Statut juridique des minorités religieuses en France Van Busterveld, Sophie C., Religious minorities and minority churches in the Netherlands Casey, James, Legal status of minority churches and religious communities in Ireland Doe, Norman, The legal position of religious minorities in the United Kingdom Duffar, Jean, La protection des droits des minorités religieuses Durham Jr., Cole W., Treatment of religious minorities in the United States Garde, Peter, Legal status of minority churches and religious communities in the Kingdom of Denmark. Liberty without equality Konidaris, J. M., Legal status of minority churches and religious communities in Greece Moran, Gloria, Legal status of minority churches and religious communities in Spain Pauly, Alexis, Statut juridique des églises et des comunautés religieuses minoritaires au Luxembourg Robbers, Gerhard, Minority churches in Germany De Sousa e Britto, Jose, La situation juridique des églises et des communautés religieuses minoritaires au Portugal Torfs, Rik, La position juridique des minorités religieuses en Belgique